ANALISIS PERSONAL HYGIENE, SANITASI LINGKUNGAN DAN KELUHAN PENYAKIT KULIT PADA PENGHUNI RUMAH SUSUN DI DESA AIR MELES ATAS KABUPATEN REJANG LEBONG - Melinda, Anggun; Widada, Agus; Gazali, Moh. (Mitra Raflesia (Journal of Health Science), 2025)
a B S T R A C TSkin disease (scabies) is identical to a community disease in areas with dense populations such as in flats. In addition, it is caused by poor personal hygiene and poor environmental sanitation that does not meet the requirements of both humidity, air temperature, lighting, clean water supply and population density. The purpose of this study was to determine personal hygiene, environmental sanitation and complaints of skin disease in Air Meles Atas Village, Rejang Lebong Regency. This research is a quantitative descriptive research that describes personal hygiene, environmental sanitation and complaints of skin diseases among flat residents in Air Meles Atas Village, Rejang Lebong Regency. This research was conducted by collecting data using questionnaires and observation, with the research subjects being 52 residents of flats. Sampling was done using total sampling technique. The research results from univariate analysis showed that more than half (71.2%) had poor personal hygiene, more than half (66.7%) the humidity of the house did not meet the requirements, more than half (66.7%) the lighting of the house did not meet the requirements, clean water supply did not meet the requirements, more than half (58.4%) population density did not meet the requirements and more than half (61,5%) positive infected skin diseases. It is hoped that all apartment residents will always maintain personal hygiene and environmental cleanliness.Keywords: Personal Hygiene, Sanitation and Skin Diseases